Monitoring of direct alcohol markers in alcohol use disorder patients during withdrawal treatment and successive rehabilitation. Issue 6 (28th January 2019) - Luginbühl, Marc; Weinmann, Wolfgang; Butzke, Ingo; Pfeifer, Philippe
Abstract: Direct and indirect biomarkers are widely applied for the determination of alcohol consumption. They help to assess past or present alcohol consumption. Depending on the window of detection and sensitivity of the investigated marker, punctual alcohol consumption may remain undetected. In this study, different sampling strategies for the intermediary long‐term marker phosphatidylethanol (PEth) are evaluated and compared to the determination of the short‐term markers ethyl glucuronide (EtG) and ethyl sulfate (EtS) in urine. Samples from 19 patients undergoing alcohol use disorder treatment were collected during the withdrawal treatment and successive rehabilitation (33 ± 26 days (range: 3–74 days)). With liquid chromatography–tandem mass spectrometry (LC–MS/MS) EtG and EtS in urine, PEth in blood, PEth in dried blood spot (DBS) from venous blood, and PEth in DBS from capillary blood were quantified and compared. The use of volumetric capillary DBS, prepared from 20 μL of blood, provided the same results as the use of venous DBS (95% ± 10%, R 2 0.9899 for PEth 16:0/18:1). Capillary DBS sampling has the advantage that it can be performed without venipuncture. The use of PEth in DBS proved to prevent post‐sampling degradation, providing a longer detection in comparison to PEth in liquid blood, which only showed 67% ± 24% of the PEth DBS 16:0/18:1 concentration. When compared with EtG and EtS in urine, PEth monitoring proved to be advantageous for the detection of relapse situations, as the accumulation of PEth in blood prolongs the detectability. In conclusion, volumetric capillary DBS sampling for PEth is a simple and useful tool for compliance monitoring, and avoids hematocrit issues. Abstract : Different sampling strategies for phosphatidylethanol (PEth) are evaluated and set side by side to EtG and EtS in urine. To compare, samples from 19 patients undergoing alcohol use disorder treatment were collected during the withdrawal treatment and successive rehabilitation. In contrast to EtG and EtS in urine, PEth was advantageous in detecting relapse situations, as the accumulation in blood prolongs the detectability. Volumetric capillary DBS sampling for PEth proved to be ideally suited for compliance monitoring, and avoids hematocrit issues.